CSF 5 - HIAA IN VIOLENT AND NON-VIOLENT SUICIDE ATTEMPTERS - Trivedi, J.K. (Medknow Publications, 1997)
Many studies have reported involvement of monoamine neurotransmission in suicide through measurement of serotonin and its main metabolite, 5-HIAA, in brain of suicide victims and in CSF of suicide attempters. 23 non-depressed non-psychotic suicide attempters and equal number of controls were selected, and all the subjects were screened on Cornell Medical Index. Suicide attempters were assessed on Risk-Rescue Rating Scale and were divided into non-violent suicide attempters (N= 12) and violent suicide attempters (N= II). CSF of all subjects was collected by lumbar puncture and CSF 5-HIAA was measured by high performance liquid chromatography with electro-chemical detector. Risk-rescue rating score was significantly higher in violent suicide attempters as compared to non-violent suicide attempters. Mean CSF- 5- HIAA was significantly lower in suicide attempters as compared to normal controls. Mean CSF 5-HIAA was significantly lower in violent suicide attempters as compared to non-violent suicide attempters.